Multiplicidade de pobrezas nas redes heterogêneas das políticas públicas contemporâneas - Curado, Jacy Corrêa (2012)
This dissertation addresses poverty as a multiple and complex phenomenon performed by a network of heterogeneous materials from contemporary public policies. To delimit these assumptions, theoretical and epistemological dialogues based on Discursive Social Psychology were articulated, addressing aspects such as the historical construction of poverty, importance of language in this construction, polysemy of meanings, and corresponding linguistic repertoires. Poverty was interpreted as a manifestation of the governmentalization of the Modern State that allowed the pursuit of a specific and complex form of government targeting the poor. Strategies for combating poverty also underwent resignifications accompanying the processes of metamorphosis and reconversion of social issues, bringing about changes in the framework of contemporary social policies, ultimately taking on the form of income transfer. To understand how the Public Policy for Combating Poverty is performed by a heterogeneous network of human and nonhuman actors through the Bolsa Família Income Allowance Program, a dialogue was articulated with selected inputs from the Actor-Network Theory and epistemological references questioning the ontological bases of truth and reality through the notions of multiplicity and performativity. Drawing on observations, interviews, conversations, and readings of public documents addressing actions of the Bolsa Família Program, three versions of "poverty" emerged: calculated, officially recorded, and controlled. These versions coexist and should not be interpreted in isolation, since taken together they would yield a joint entity or comprise a portrait of poverty that is homogeneous, stable, and permanent, understood from diverse viewpoints and perspectives. By contrast, a focus on a multiplicity of poverties is proposed in the present study. Connections between and bifurcations from versions of poverty produced by the materialities and socialities of the heterogeneous network of public policies for combating poverty are also highlighted, in a bid to destabilize, deterritorialize, and impart flexibility to the traditional notions of poor and poverty"